New wood dust reinforced recycled polypropylene composite filament and traditional polypropylene filament for FDM applications: Life cycle assessment study - Yusuf, Yusliza; Wong, Chun Yip; Mohammad Taha, Mastura; Mustafa, Nuzaimah; Che Daud, Zuraidawani (Universiti Malaysia Terengganu, 2023)
Life Cycle Assessment (LCA) is an effective method for determining the environmental impact of a composite material over its lifetime. Consequently, it is important to the composites sector, particularly for Fused Deposition Modelling (FDM) filament manufacturers as a material selection tool when determining the usability of recycled material utilised in component design phases. This article investigates the LCA framework of utilising wood dust as reinforced material and recycled polypropylene material in the production of composite filament for the FDM sector. Eco Audit, a feature of the CES Edupack programme, was utilised to evaluate the LCA from an environmental standpoint for product makers. Using recycled polypropylene containing an increasing weight percentage of wood dust to produce new types of composite filament materials reduces energy consumption (MJ) and lowers the carbon footprint (kg). This is because the quantity of energy required for recycling is far less than that required for initial manufacture. When compared to the new polypropylene material that is used to create filament, this study reveals a 56% and 37% reduction in energy consumption and CO2 emissions, respectively. This is a considerable improvement from an environmental point of view.